EFFECTIVENESS OF A NURSE-LED TRAINING PROGRAM IN IMPROVING THE KNOWLEDGE AND SKILLS ON BASIC LIFE SUPPORT AMONG NEWLY HIRED NURSES AT UNIVERSITY MEDICAL CENTER - Baizulda, Aida; Amangeldiyeva, Akbota; Yeleussiz, Assyltas; Metchenova, Gulsharat; Maratkyzy, Ayaulym (Nazarbayev University School of Medicine, 2025)
Introduction: Sudden cardiac arrest is one of the most common causes of death worldwide. Since patients with cardiovascular diseases are at high risk of circulatory arrest, it was essential for the University Medical Center (UMC) to train every staff member in Basic Life Support (BLS). Understanding that nurses spend the most time with patients, we decided to focus our research on assessing the knowledge of nurses. Methods: This study utilized a one-group pre-test and post-test design, and was conducted at the University Medical Center (UMC) in Astana, Kazakhstan. A convenience sample of 49 nurses participated in the study. A nurse-led BLS training program following the European Resuscitation Council standards was implemented. The knowledge questionnaire and the skills checklist used to collect the data were adapted from the European Resuscitation Council. BLS knowledge and skills were assessed before the intervention, immediately after the intervention, one- and two-month after the intervention. Repeated measures Analysis of Variance (ANOVA) with Greenhouse-Geisser correction was performed to examine the differences in the BLS skills between the three data collection times. Paired samples t-test was performed to examine the knowledge scores between pre-test and post-test 1, and between post-test 1 and post-test 2. Results: These findings showed that the BLS training improved the nurses’ BLS knowledge immediately after the training, but the knowledge level declined just after one month of the training. For the skills, these findings indicated that the BLS training was effective in improving the BLS skills of the nurses immediately after the intervention, and the BLS skills level was consistently improved significantly until one-month post-training. Conclusion: The results demonstrated a significant improvement in both BLS knowledge and practical skills immediately after the intervention. Notably, skill scores continued to improve over time, while knowledge retention declined after one month. These findings underscore the value of simulation-based and nurse-led training programs in clinical onboarding processes, while also pointing to the need for structured knowledge reinforcement strategies to maintain cognitive gains.
Keywords: Basic Life Support; Knowledge; Nurse; Skills; Training; type of access: embargo